DNA barcoding revealing the occurrence of Isarachnanthus (Cnidaria; anthozoa; ceriantharia) in cape Verde - Stampar, Sérgio Nascimento [UNESP]; Lopes, Celine S.S. [UNESP]; De Angelis, Stefany Archangelo [UNESP]; Morandini, André Carrara (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
The occurrence of Isarachnanthus Carlgren, 1924 (Cnidaria: Anthozoa: Ceriantharia) specimens in Cape Verde Islands is recorded. Identification of the tube anemone species Isarachnanthus maderensis (Johnson, 1861) was possible based on DNA Barcoding. A discussion on biogeographic patterns associated with ocean circulation and life cycle is presented.
Keywords: Biogeography; Marine Invertebrates; Taxonomy